Ultrahigh-resolution 3D monitoring reveals sediment-derived plumes as algal bloom precursors - Xiao, Peng; Zhang, Congchao; Tao, Yu; Xu, Tiefu; Chen, Ying; Feng, Lian; Kong, Lingchao; Wen, Zhidan; Zheng, Weibin; Xu, Hao; Guo, Longxin; Guo, Hangyu; et al. (Elsevier, 2026)
The global intensification of harmful algal blooms severely compromises freshwater ecosystems, threatening biodiversity and critical ecosystem services through toxin exposure, hypoxia, and water quality degradation. Bloom formation involves a complex interplay of nutrient dynamics, hydrology, and microbial activity. Although subsurface processes—such as the release of sediment-bound nutrients and the germination of dormant cyanobacteria—are thought crucial to bloom initiation, these phenomena occur at fine spatiotemporal scales beyond the reach of conventional monitoring. As a result, the exact, rapidly evolving triggers of bloom emergence remain mostly unknown. Here we show meter-scale chlorophyll a (Chl-a) plumes rising from the sediment–water interface, triggered by heavy rainfall and directly seeding surface blooms. We captured these dynamics using a custom underwater drone that collected over 2.8 million data points at 5-m horizontal and 1-m vertical resolution. Algal blooms exhibit a clear vertical sequence: anomalous Chl-a levels first appear in deep benthic layers after rainfall-driven resuspension, then intensify simultaneously across near-bed depths, and finally reach the surface after a median lag of 0.8–1.5 days. These observations provide in situ evidence associating benthic algal seed stocks with surface bloom initiation, revealing that the origin and spatial heterogeneity of such events arise from rainfall-driven disturbances at the sediment–water interface. This robotic approach not only deciphers the subsurface origins of algal blooms but also empowers predictive modeling and adaptive management strategies, advancing global efforts to combat eutrophication amid escalating climate pressures and safeguard vital water resources.
Keywords: 40 Engineering; 41 Environmental Sciences; Climate-Related Exposures and Conditions; 6 Clean Water and Sanitation; 4011 Environmental engineering; 4103 Environmental biotechnology; 4104 Environmental management; Harmful algal blooms (HABs); Sediment-derived plumes; Ultrahigh-resolution; Three-dimensional (3D) monitoring; Early warning